Drying/encapsulation of red wine to produce ingredients for healthy foods - Álvarez Gaona, Izmari Jasel (2017)
Fil: Álvarez Gaona, Izmari J. Pontificia Universidad Católica Argentina. Facultad de Ingeniería y Ciencias Agrarias; Argentina